Development Of A Plant Regeneration System And Analysis Of 101 Heat Shock Protein In Strawberry Cv. Camarosa Following Gene Bombardment - Haddadi, Fatemeh (2009)

(untitled)
The aims of this study were to develop in vitro regeneration system and to confirm the transient expression of HSP101 gene via protein analysis in strawberry cv. Camarosa. In the in vitro study, two types of explants which were shoot tips derived from runner tips and leaves were used. Different types of cytokinins such as BAP, TDZ and zeatin at different concentrations were assessed for shoot induction, while the auxins IBA and NAA also at different concentration were used in the root induction experiment. The experiments were conducted in a Randomized Complete Block Design (RCBD). In the shoot induction experiment using shoot tips cultured on different concentrations and combinations of TDZ and BAP, MS medium supplemented with 4 μM BAP in combination with 2 μM TDZ was optimum for strawberry shoot proliferation. In the shoot induction experiment from shoot tips using zeatin, the highest percentage of explant producing shoots and number of shoots formed per explant were obtained on MS medium containing 4 μM zeatin. High frequency of shoot regeneration from strawberry leaves using different concentrations and combinations of BAP and TDZ was achieved on MS medium containing 4 μM TDZ, without BAP. In the rooting study, MS medium containing 1 μM NAA, MS medium containing 1 μM IBA and MS medium without auxins, were most suitable in inducing the highest number of roots per explant, highest percentage of root formation and the longest root, respectively. Biolistic method of gene transfer has the advantage of allowing a fast and rapid analysis, and was therefore selected for transient expression of HSP101 gene in strawberry via protein analysis. In this study, in vitro leaf explants of strawberry were used. Transient gene expression assays of the AtHSP101 gene showed that this gene can be transiently expressed in strawberry plants. An additional faint protein band of approximately 100 kD was observed on SDS polyacrylamide gel electrophoresis after bombardment of the leaf explant with plasmid, which most probably corresponded to the HSP101 encoded product. In the study on total protein assay using Bradford method, the amount of total protein after bombardment of leaf explant with plasmid containing HSP101 gene increased in comparison with bombardment without plasmid and with non bombarded explants. This result also confirmed that this gene can be transiently expressed in strawberry plants. Therefore by using the regeneration protocol obtained in this study and HSP101 gene which can be transiently expressed, genetic engineering of strawberry cv. Camarosa for heat tolerance can be achieved.